Web design : interactive and games. - Wiedemann, Julius, ....- (Hong Kong : Taschen)
100 prime examples from the world's best digital agencies demonstrating the key role interactivity plays on the web todayWith its origins tied to the invention of the hyperlink, the web is defined by interaction. In the internet's early days, interaction consisted on clicking links to be taken to different pages. Today, with broadband, flash, video, sound, and online games, this concept has been taken to another level. From news sites and blogs to commercial and public awareness sites, interactivity is the key to the internet experience. This book showcases about 100 examples of work from the world's best digital agencies-such as Greenpeace, Volkswagen, and Nike-demonstrating the most innovative uses of interactivity on the web today.